Copper for America : The United States Copper Industry from Colonial Times to the 1990s - Hyde, Charles K., 1945- (Book collections on Project MUSE., 1998)
This comprehensive history of copper mining tells the full story of the industry that produces one of America's most important metals. The first inclusive account of U.S. copper in one volume, Copper for America relates the discovery and development of America's major copper-producing areas--the eastern United States, Tennessee, Michigan, Montana, Arizona, New Mexico, Nevada, Utah, and Alaska--from colonial times to the present. Starting with the predominance of New England and the Middle Atlantic states in the early nineteenth century, Copper for America traces the industry's migration to Michigan in mid-century and to Montana, Arizona, and other western states in the late nineteenth century. The book also examines the U.S. copper industry's decline in the twentieth century, studying the effects of strong competition from foreign copper industries and unforeseen changes in the national and global copper markets. An extensively documented chronicle of the rise and fall of individual mines, companies, and regions, Copper for America will prove an essential resource for economic and business historians, historians of technology and mining, and western historians.